Round Numbers Can Sharpen Cognition - Nguyen, Huy Anh; Hofman, Jake; Goldstein, Daniel G. (CHI 2022, 2022)
Scientists and journalists strive to report numbers with high precision to keep readers well-informed. Our work investigates whether this practice can backfire due to the cognitive costs of processing multi-digit precise numbers. In a pre-registered randomized experiment, we presented readers with several news stories containing numbers in either precise or round versions. We then measured their ability to approximately recall these numbers and make estimates based on what they read. Our results revealed a counter-intuitive effect where reading round numbers helped people better approximate the precise values, while seeing precise numbers made them worse. We also conducted two surveys to elicit individual preferences for the ideal degree of rounding for numbers spanning seven orders of magnitude in various contexts. From the surveys, we found that people tended to prefer more precision when the rounding options contained only digits (e.g., "2,500,000") than when they contained modifier terms (e.g., "2.5 million"). We conclude with a discussion of how these findings can be leveraged to enhance numeracy in digital content consumption.